2009
DOI: 10.1080/09537100802409921
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pitavastatin, eicosapentaenoic acid and combined therapy on platelet-derived microparticles and adiponectin in hyperlipidemic, diabetic patients

Abstract: Platelet-derived microparticles (PDMP) play an important role in the pathogenesis of diabetic vasculopathy, and statins or eicosapentaenoic acid (EPA) have been shown to have a beneficial effect on atherosclerosis in hyperlipidemic patients. However, the influence of EPA and statins on PDMP and adiponectin in atherosclerosis is poorly understood. We investigated the effect of pitavastatin and EPA on circulating levels of PDMP and adiponectin in hyperlipidemic patients with type II diabetes. A total of 191 hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 43 publications
1
67
0
2
Order By: Relevance
“…13) Nomura, et al clearly showed that platelet-derived microparticles, indicating platelet activation, signifi cantly decreased with EPA treatment in hyperlipidemic and diabetic patients. 14) Conversely, several studies failed to show any antiplatelet effects of EPA. Davi, et al studied the add-on effect of EPA with ticlopidine on platelet function in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…13) Nomura, et al clearly showed that platelet-derived microparticles, indicating platelet activation, signifi cantly decreased with EPA treatment in hyperlipidemic and diabetic patients. 14) Conversely, several studies failed to show any antiplatelet effects of EPA. Davi, et al studied the add-on effect of EPA with ticlopidine on platelet function in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary EPA has successfully suppressed the expression of platelet activation markers and the release of platelet-derived microparticles capable of generating thrombin (a potent platelet aggregator), thereby retarding further platelet activation [17,18]. There is evidence that EPA and DHA also reduce platelet aggregation [19].…”
Section: Introductionmentioning
confidence: 95%
“…EPA alone decreased insulin reactivity and increased adiponectin levels in obese Japanese, without affecting leptin levels (114) . In type 2 diabetics, EPA had no effect on adiponectin levels but an additive positive effect when combined with statin treatment (194) . To date, only three studies investigated the independent effects of EPA and DHA on insulin sensitivity in human subjects.…”
Section: Insulin Sensitivity and Glycaemic Controlmentioning
confidence: 99%